THE RELATIONSHIP BETWEEN POWER DISTANCE AND COMPULSIVE PERCEPTION OF CITIZENSHIP BEHAVIOR: MEDIATING EFFECT OF SUPERVISOR-SUBORDINATE GUANXI, MODERATING EFFECT OF WORKPLACE CLIMATE - Ching-Ru Cheng; Pei-Chieh Kuan; Tsai-Jung Wu; Yi‐Hsien Wang (PEOPLE: International Journal of Social Sciences, 2025)
This study examines the relationship between power distance and compulsive perception of citizenship behavior from the perspective of social exchange theory, with supervisor-subordinate guanxi as the mediating effect and workplace climate as the moderating effect. A quantitative research method was used to collect data through a questionnaire survey, and the target population was employees of various industrial enterprises in Taiwan. This study found that power distance and supervisor-subordinate guanxi significantly related to compulsive perception of citizenship behavior, indicating that compulsive perception of citizenship behavior is not only affected by power distance, but also by supervisor-subordinate guanxi. The results of this study have important implications for human resource management practices, especially in compulsive perception of citizenship behavior. The study suggests that companies should promote informal communication and interaction between supervisors and employees, such as dinner parties, in order to reduce the negative impact of compulsive perception of citizenship behavior by reducing power distance.